Contribution of differential diversification rates to current broad-scale patterns os species richness in south american birds (2010)
Multiple studies have revealed relationships between current spatial patterns of species richness and various environmental factors. However, little is known about the origin of these relationships in terms of processes of speciation, extinction, and immigration. The diversification rate hypothesis holds that correlations between spatial patterns of current richness and environmental factors result from spatial variation in diversification, the balance between speciation and extinction. Variants of this hypothesis propose mechanisms by which particular environmental factors may affect current richness through their effect on diversification. The species-energy hypothesis proposes that energy availability increases diversification through its effect on the number of individuals co-occurring in an area and concomitant decrease in extinction rate or increase speciation rate. The evolutionary speed hypothesis suggests that higher temperatures increase speciation rate by increasing mutation rates and decreasing generation times. The spatial heterogeneity hypothesis asserts that spatial variation in environmental conditions within an area increases diversification because it fosters speciation by increasing opportunities for isolation and ecological divergence, or because it decreases extinction rates by allowing species to track climatic oscillations more readily. Empirical studies assessing the relative importance of the diversification rate hypothesis and its variants are rare. Here, we used a database on the spatial richness pattern of suboscine birds across South America in conjunction with a time-calibrated phylogeny to measure how much of the current spatial variance in richness can be explained by the diversification rate hypothesis and its variants.